"Speak from every mouth – the speech, a poem": conflicting voices, discourses and identities in the poetry of Robert Browning - Guimarães, Paula Alexandra (2011)
'XII Colóquio de Outono. Vozes, Discursos e Identidades em Conflito' (org. A.G. Macedo et al), Centro de Estudos Humanísticos da Universidade do Minho.